EKONOMI ISLAM (SUATU TINJAUAN METODOLOGIS ISLAM) - Nurhayati . (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2014)
Following the birth of postmodernism modernism helplessness in addressing the issues of modern human life, opening up more space for Muslims to re-offer and demonstrate the existence of a methodology based on Islamic values. This prompted the Muslim intellectuals to formulate a methodological framework with methods and approaches that address the challenges of the times. One of them makes â€œmaqa>sid al-shari>'ahâ€, which led to the benefit of mankind, as the Islamic approach to science as a whole, including the methodology of Islamic economics. Islamic economic method is largely determined by its world view, as a method refers to the rules and procedures of a discipline that followed a certain logic in order to achieve the desired goal. Efforts made by Muslim intellectuals is to bring the discipline of fiqh (Islamic law) to the integral Philosophy of Islamic Law and not dichotomous, ie unification with the legal aspects of moral values, so as to melt the rigidity of Islamic law and give spirit to the moral values of Islamic economy.